1987
DOI: 10.1104/pp.85.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Peroxisomal Active Oxygen-Related Enzymes in Copper-Tolerant Pea Plants

Abstract: The effect in vivo of high nutrient levels of copper (240 micromolar) on the activity of different metalloenzymes conaining Cu, Mn, Fe, and Zn, distributed in chloroplasts, peroxisomes, and mitochondria, was studied in leaves of two varieties ofPisum satiRvum L. plants with different sensitivity to copper. The metalloenzymes studied were: cytochrome c oxidase, Mn-superoxide dismutase (Mn-SOD) and Cu,Zn-superoxide dismutase I (Cu,Zn-SOD I1), for mitochondria; catalase and Mn-SOD, for peroxisomes; and isozyme C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 21 publications
5
22
0
Order By: Relevance
“…Therefore, in addition to their predicted signaling role, they could also act directly. Cytochemical studies have shown that the accumulation of ROS is related to rapid cell death in infected cells and is correlated with a rapid loss of membrane integrity [30]. Results for MDA production in investigated soybean leaves were very similar to those for .…”
supporting
confidence: 64%
“…Therefore, in addition to their predicted signaling role, they could also act directly. Cytochemical studies have shown that the accumulation of ROS is related to rapid cell death in infected cells and is correlated with a rapid loss of membrane integrity [30]. Results for MDA production in investigated soybean leaves were very similar to those for .…”
supporting
confidence: 64%
“…SOD activity increased in C71 stem 3-times at 48 h post inoculation compared to control. Numerous reports also showed an increase in SOD activity in plants under oxidative stress (Palma et al 1987;Gupta et al 1993;Kang & Saltveit 2002;Chan et al 2007;Asthir et al 2010). Malencic et al (2004Malencic et al ( , 2010 found that the SOD activity increase in sunflower and soybean lines with increasing oxalic acid concentration as well as inoculation with S. sclerotiorum.…”
Section: Resultsmentioning
confidence: 99%
“…The net result was an unchanged total SOD capacity (Cardinaels et al, 1984). Palma et al (1987) demonstrated that the specific activity of peroxisomal Mn-SOD in the leaves of Pisum sativum was higher in copper-tolerant than in non-tolerant plants and suggested that this increased activity could play a role in the copper tolerance mechanism of this plant. De Vos (1991) found an increase of both Cu-Zn-SOD and Mn-SOD in roots of copper sensitive Silene cucubalus after supply of toxic concentrations of copper.…”
Section: Superoxide Dismutasementioning
confidence: 99%